Association Study of the M132L Single Nucleotide Polymorphism With Susceptibility to Chronic Wasting Disease in Korean Elk: A Meta-Analysis - Roh, In-Soon; Kim, Yong-Chan; Won, Sae-Young; Park, Kyung-Je; Park, Hoo-Chang; Hwang, Ji-Yong; Kang, Hae-Eun; Sohn, Hyun-Joo; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Chronic wasting disease (CWD) is a deleterious brain proteinopathy caused by a pathogenic form of prion protein (PrPSc), which is converted from a benign form of prion protein (PrPC) encoded by the prion protein gene (PRNP). In elks, the M132L single nucleotide polymorphism (SNP) of the PRNP gene likely plays a pivotal role in susceptibility to CWD. However, the association of the M132L SNP with susceptibility to CWD has not been evaluated in Korean elk to date. To estimate the association of the M132L SNP with susceptibility to CWD in Korean elk, we investigated the genotype and allele frequencies of the M132L SNP by amplicon sequencing and performed association analysis between CWD-positive and CWD-negative elks. In addition, we performed a meta-analysis to evaluate the association between the M132L SNP and susceptibility to CWD in quantitatively synthesized elk populations. Furthermore, we estimated the effect of the M132L SNP on elk PrP using in silico programs, including PolyPhen-2, PROVEAN, AMYCO and Swiss-PdbViewer. We did not identify a significant association between the M132L SNP of PRNP and susceptibility to CWD in Korean elks. The meta-analysis also did not identify a strong association between the M132L SNP of PRNP and susceptibility to CWD in quantitatively synthesized elk populations. Furthermore, we did not observe significant changes in structure, amyloid propensity or electrostatic potential based on the M132L SNP in elk PrP. To the best of our knowledge, this was the first report of an association analysis and meta-analysis in Korean elks and quantitatively synthesized elk populations, respectively.